Evaluation of the thermal comfort of beef cattle in feedlot in hot weather - Zazueta G., Citlaly (2021)
The thermal comfort of beef cattle in intensive finishing was assessed through the availability of shade and living space, in conditions of the very hot semi-dry climate of the northwestern coastal region of Mexico during autumn and winter and housed in three types of pens. The design of the pens varied according to the infrastructure available in the livestock production unit (pen area and shade per animal). The observation period was six weeks per season. The daily ambient temperature and relative humidity were measured, and the Temperature and Humidity Index (ITH) was calculated. The area of each pen, the shade area, and the number of cattle per pen were measured to calculate the living space and the shade available at the beginning and at the end of the fattening period. In autumn, the cattle were in a state of Danger to Emergency Thermal (ITH ≥84 units) and in the winter in a state of Thermal Alert (ITH ≥70). The provision of living space and shade was insufficient in both seasons and periods according to indicators for confined meat-producing cattle, regardless of the pen design.